EKSISTENSI THE EXISTENCE OF QUARTER LIFE QRISIS PHENOMENON IN YOUNG ADULTS ON MENTAL HEALTH PRE-COVID-19 AND DURING COVID-19 IN THE COMMUNITY OF THE CITY OF PAREPARE - M. Natsir; Abidin Abidin; Try Ayu Patmawati; Wajdi, Muhammad (International Journal of Multidisciplinary Research and Studies, 2022)
The formulation of the problem in this study are; (1) What is the impact of the quarter-life crisis, on adulthood before and before the pandemic; (2) How do the quarter-life crises in early adulthood affect mental health; (3) The effect of the Workshop on people who feel lost and even experience a quarter-life crisis. The aims of this study were: (1) to find out how the impact of the quarter-life crisis in early adulthood and before the pandemic; (2) to know the impact of the quarter-life crisis in early adulthood on mental health; (3) to Knowledge of the influence of the Workshop on people who feel lost and even experience the Crisis of a quarter of life. The benefits of this research. This type of research is exhibition fact research. The results showed that there was an effect of the quarter-life crisis on the prevention of Covid-19 in the people of Pare-Pare City as indicated by the value of Sig. 0.002 < 0.005 and there is an effect of a quarter of life crisis on mental health in the people of Pare-Pare City with a value of Sig. 0.014<0.05.